Preservation of functionality of Bifidobacterium animalis subsp. lactis INL1 after incorporation of freeze-dried cells into different food matrices - Vinderola, Celso Gabriel (2012)
The aim of this work was to investigate how production and freeze-drying conditions of Bifidobacterium animalis subsp. lactis INL1, a probiotic strain isolated from breast milk, affected its survival and resistance to simulated gastric digestion during storage in food matrices. The determination of the resistance of bifidobacteria to simulated gastric digestion was useful for unveiling differences in cell sensitivity to varying conditions during biomass production, freeze-drying and incorporation of the strain into food products. These findings show that bifidobacteria can become sensitive to technological variables (biomass production, freeze-drying and the food matrix) without this fact being evidenced by plate counts.